The Impact of Centre-Based Childcare on Non-cognitive Skills of Young Children - Greta Morando; Lucinda Platt (Institute of Labor Economics (IZA), 2022)
The early development of non-cognitive skills has longlasting benefits for children's sub- sequent educational attainment and wages. Drawing on a rich, nationally representative longitudinal sample of young children in Ireland, we present new evidence on whether the use of centre-based childcare (CBC) in infancy and early years promotes non-cognitive skills by school entry. We focus on the type of non-parental childcare used by mothers who are working when their child is nine months, comparing CBC with other form of non-parental care. We consider the impact of childcare type on three domains of socio-emotional skills: externalising, internalising and pro-social behaviours. We find negative effects of CBC on both externalising and pro-social behaviours across most specifications. With a cumulative value added model we estimate that centre-based childcare at age three worsens externalising behaviour at age five by 0.11 standard deviations compared to other forms of non-parental care. This is equivalent to 44% of the difference in externalising behaviour between children with a mother with/out tertiary education. The effect of CBC on the externalising dimension of socio-emotional skills of children entering school is consistent across several specifications and robustness checks. Given planned expansion of CBC for those needing subsidised provision, we conclude that such measures could exacerbate socio-emotional inequalities.
Keywords: J13; J24; I21; I24; 330; centre-based childcare; child socio-emotional development; non-cognitive skills; growing up in Ireland